Design of an Off – Grid Solar Power System for the Shashi Baby and Kids Food Industry in Bukittinggi - Laksono, Dedi Tri; Laksono, Deni Tri; Fahmi, Monika Faswia; Dodi, Nofri (International Journal of Science, Engineering, and Information Technology, 2024)
The transition to renewable energy is increasingly important in addressing global energy demands and environmental issues. Solar energy has emerged as a sustainable option, particularly for small and micro businesses that often face challenges related to energy supply and costs. Shashi Baby and Kids Food, a micro – enterprise producing baby food, can benefit from an off – grid solar power system to support its operational needs, especially lighting during the night. The system design involves analyzing energy requirements, selecting solar panels, batteries, inverters, and simulating the system using PVsyst software to optimize performance. This system is designed to support operations with nine lamps for 12 hours a day, generating sufficient energy and ensuring adequate storage. Simulation results show that the system has a performance ratio (PR) of 75.86% and a solar fraction (SF) of 99.82%, indicating high efficiency and nearly fully meeting energy needs through solar power. Although there is a slight decrease in SF in December, this system design has proven to be efficient and reliable in supporting business operations. Further analysis reveals that the annual energy production reaches 1451 kWh, with specific production of 1210 kWh per kWp, confirming that this system can generate significant energy for the operational needs of the business.